Perlindungan Hak Peserta Program Magang di Hotel XYZ Kota Bandung - Danurdara, Ananta Budhi (Politeknik Pariwisata NHI Bandung, 2018)
Apprenticeship program is one part of the laborrs force in Indonesia, apprentices basically get the same protection with other labors, but in Indonesia there are many industries that do not provide rights that should be given to participants of the internship program. The purpose of this study was to determine, assess, examine and analyze how the legal protection for participants in apprenticeship programs and practices to determine, assess, examine and analyze an obstacle in the implementation of the apprenticeship program. Study used is descriptive nature Analytical. Secondary data was obtained from the research literature and reinforced with Primary Data obtained from interviews daan questionnaire. Stages of the research literature research and field research. Techniques of data collection are through literature study and interviews. Methods of data analysis using Likert method. The results showed that the occurrence of violations of rights protection for participants in the company's apprenticeship program in terms of three main components, namely Statutory Rights, Contractual Rights and Other Rights on the Protection of Rights Internship Program participants have not been frilly implemented in practice yet. This is because there are some companies who do not exercise rights apprenticeship program participants in the form of the right to obtain employment injury insurance and the right to earn pocket money and or transport money and not doing the apprenticeship agreement in writing between the parties with the company's apprenticeship program participants in a company. Other authors propose recommendations for the educational institutions and industry especially Hotel XYZ at Bandung management to address the existing problems. The purpose of these recommendations is to provide input to the hotel in order to provide protection Rights Internship Program Participants in accordance with the rules of government.